Succeed or succumb? - Samai, Whahaedea; Hassan, Arif (Management Centre, IIUM, 2012)
The case study primarily deals with the analysis of two different, rather opposing styles of leadership and their resultant effects on the personality, attitude and performance of the subordinate employees. This case details the characteristics of a bossy, authoritative, prejudiced, close-minded, and destructive critical leader whose approach to dealing with subordinate staff lowers an employee’s morale, leads to lower productivity and even forces one to quit the job; whereas on the other hand, it shows a participative, open-minded, supportive, amicable, and friendly leader who is able to boost employee morale and enhance motivation to work harder, while being committed to the organisation. This case study also provides an illustration of the fact that sometimes, in order to succeed and get promoted in an organisation, we may have to put aside our personal relationships in the workplace, or even walk over them to climb the ladder of success.